Harnessing the Multifunctionality in Nature: A Bioactive Agent Release System with Self‐Antimicrobial and Immunomodulatory Properties. Issue 13 (September 2015) - Özçelik, Hayriye; Vrana, Nihal Engin; Gudima, Alexandru; Riabov, Vladimir; Gratchev, Alexei; Haikel, Youssef; Metz‐Boutigue, Marie‐Hélène; Carradò, Adele; Faerber, Jacques; Roland, Thierry; Klüter, Harald; Kzhyshkowska, Julia; et al.
Abstract : Major problems with biomedical devices in particular implants located in nonsterile environments concern: (i) excessive immune response to the implant, (ii) development of bacterial biofilms, and (iii) yeast and fungi infections. An original multifunctional coating that addresses all these issues concomitantly is developed. A new exponentially growing polyelectrolyte multilayer film based on polyarginine (PAR) and hyaluronic acid (HA) is designed. The films have a strong inhibitory effect on the production of inflammatory cytokines released by human primary macrophage subpopulations. This could reduce potential chronic inflammatory reaction following implantation. Next, it is shown that PAR, due to its positive charges, has an antimicrobial activity in film format against Staphylococcus aureus for 24 h. In order to have a long‐term antimicrobial activity, a precursor nanoscale silver coating is deposited on the surface before adding the PAR/HA films. Moreover, the PAR/HA films can be easily further functionalized by embedding antimicrobial peptides, like catestatin (CAT), a natural host defense peptide. This PAR/HA+CAT film proves to be effective as an antimicrobial coating against yeast and fungi and its cytocompatibility is also assessed. Finally, this all‐in‐one system constitutes an original strategy to limit inflammation and prevents bacteria, yeast, and fungi infections. Abstract : Adverse immune reaction to implants and bacterial/fungal infections around implants constitute major clinical problems. In this study, a natural antimicrobial peptide (catestatin) loaded into polyelectrolyte multilayer films based on polyarginine and hyaluronic acid is shown to have both immunomodulatory and antibacterial effects due to the multifunctionality of the coating components.